(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Integration is a relatively new approach in pedagogy, the introduction of which can increase the level of the educational process the rising generation. Integration in pedagogy and education is, first of all, the interaction of various elements of any systems in order to obtain something holistic, new. The concept of "system" in modern pedagogy can be used in different aspects, for example: educational institution as a system; educational system classes; the system of relationships between learners and teachers, etc.